Thermochromic Narrow Band Gap Phosphors for Multimodal Optical Thermometry: The Case of Y3+-Stabilized β‑Bi2O3:Nd3 - Back, Michele; Xu, Jian; Ueda, Jumpei; Benedetti, Alvise; Tanabe, Setsuhisa (Chemistry of materials, 2022)
The design and development of effective luminescent thermal sensors have been driving technological progress in many different fields ranging from catalysis to biology and microelectronics, to name a few. The ratiometric concept of using the ratio between two luminescent emissions of lanthanide-doped phosphors allows overcoming some limitations resulting from the single emission-based thermometers. A fundamental requirement for the development of effective luminescent thermometers relies on efficient luminescence output, which is not always accessible. Therefore, alternative methods to probe the temperature in a reliable and simple way are still a challenge. Despite the conventional limits of using narrow band gap materials as hosts for lanthanoid ions, a smart design allows for the development of unusual phosphors with appealing properties. By taking advantage of the narrow band gap of Bi2O3 polymorphs, here we demonstrate the potential of the tetragonal Y-stabilized β-Bi2O3:Y3+,Nd3+ system as a multimodal thermometer combining the conventional Boltzmann thermometry based on Nd3+ together with the thermochromism of the host. With the aim of testing this new concept, the temperature dependence of the reflectance spectra was investigated. Moreover, from the application point of view, the chromaticity variations of the material described by means of simple thermometric parameters such as the ratio a*/b* and the hue angle h ab are demonstrated to be particularly promising and already implemented in software commonly used worldwide. The results suggest the potential of the strategy of combining narrow band gap semiconductors with lanthanoid ions to design reliable and multimodal thermal sensors, paving the way to a new family of thermochromic and luminescent thermal sensors.